Strategi Peningkatan Pendapatan Petani Kelapa Sawit Swadaya di Kecamatan Kalis - Andriyani Andriyani; Adi Suyatno; Dewi Kurniati (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2026)
Strategies to increase the income of self -help palm oil farmers can help farmers to increase production yields. This study aims to formulate and obtain strategies in an effort to increase the income of oil palm farmers. This research was conducted in Kalis District, Kapuas Hulu Regency. This study was carried out from April 5 to May 524. This study used a descriptive quantitative method with case study methods and identified internal factors (strengths and weaknesses) and external (opportunities and threats) used for the strategy to increase the income of oil palm farmers in the sub -district dull. The variables used in this study were obtained from indicators of strengths, weaknesses, opportunities and threats. Based on the results of the research results of the collection, processing and analysis of the main internal factors, it is found that the main strength factor of farmers is the status of land ownership and land area owned by farmers with a weight score of 0.41. As for the main weakness of self -help farmers is inadequate access to infrastructure with a weight score of 0.18 and the total score of the IFE matrix is ​​2.51. For data analysis of the main external factors, it is found that the main opportunity factor of farmers is oil palm can be a term investment for farmers with a weight score of 0.41. As for the main threat of self -help farmers is a long queue at the Palm Oil Mill (PKS) with a weight score of 0.18 and the total score of the IFE matrix is ​​2.62. The results of processing internal and external data of farmers using the IE matrix show that the position of farmers is in quadrant I, the suitable strategy is an aggressive strategy that can support the growth of oil palm farming.